Structural and Spectral Analysis of Anticancer Active Cyclo(Ala-His) Dipeptide - Çelik, Sefa; YILMAZ, GÖZDE; Özel, Ayşen E.; AKYÜZ, SEVİM (Taylor & Francis Inc., 2020)
The theoretically possible most stable conformation of the cyclic dipeptide, which has a significant anticancer activity, was examined by conformational analysis method and then by DFT calculations. With DFT calculations, cyclo(Ala-His) dipeptide was found to be more stable in boat form than in planar conformation. Moreover, conformations of the dimeric forms of the title molecule were investigated. The dimeric forms of the cyclo(Ala-His) dipeptide were created by combining two identical cyclo(Ala-His) monomers, in lowest energy configuration and as a result three energetically possible dimeric structures were obtained. The solid phase FTIR and Raman spectra of cyclo(Ala-His) have been recorded. The spectra were interpreted with the aid of quantum chemical calculations based on density functional theory, using B3LYP and wb97xd methods with 6-311++G(d,p) basis set, in order to elucidate structural and spectral properties of the investigated molecule. Experimental vibrational spectra are found to be in accord with the simulated vibrational spectra. The assignment of the vibrational modes was performed depending on the calculated potential energy distribution (PED).In slicomolecular docking of cyclo(Ala-His) was also carried out with DNA. The drug likeness and ADMET properties were analyzed for the prediction of pharmacokinetic profiles. The results revealed that the compound has the potential to be the leading molecule in the drug discovery process.
Keywords: Cyclo(Ala–His); Cyclic Dipeptide; DFT Calculations; Molecular Docking; ADMET